Does Africa Need a Rotten Kin Theorem? Experimental Evidence from Village Economies - Jakiela, Pamela (World Bank, Washington, DC, 2012)
This paper measures the economic impact of social pressure to share income with kin and neighbors in rural Kenyan villages. The authors conduct a lab experiment in which they randomly vary the observability of investment returns. The goal is to test whether subjects reduce their income in order to keep it hidden. The analysis finds that women adopt an investment strategy that conceals the size of their initial endowment in the experiment, although that strategy reduces their expected earnings. This effect is largest among women with relatives attending the experiment. Parameter estimates suggest that women behave as though they expect to be pressured to share four percent of their observable income with others, and substantially more when close kin can observe income directly. Although this paper provides experimental evidence from a single African country, observational studies suggest that similar pressure from kin may be prevalent in many rural areas throughout Sub-Saharan Africa.